PENGARUH KESADARAN DAN PENGETAHUAN TERKAIT KEAMANAN PRODUK TERHADAP NIAT PEMBELIAN PRODUK KECANTIKAN DAN PERAWATAN KULIT DI MASYARAKAT JABODETABEK - Nattassha, Ruth; Roshni, Roshni; Viviana, Viviana (Universitas Nusa Cendana, 2024)
The rise of the beauty and skincare industry in Indonesia is accompanied by a glaring issue of this industry: the existence of illegal products without certification National Agency of Drug and Food Control which possibly contain substances harmful to skin health. Even with the existence of said certification, it is evident that there are demands for such products. The question arises from such a phenomenon: are the Indonesian consumers of beauty and skincare products aware of the certification, and are they using said information in their purchase decision? This research is conducted to find the answers to those questions, by utilizing the theory of planned behavior expanded with awareness and knowledge variables. A study of 72 consumers in Jabodetabek shows that while they have both the awareness and knowledge about the safety of said products, their attitude towards uncertified products has more effect on their intention to purchase compared to other variables. Keywords: Theory of Planned Behavior; Product Knowledge; Product Safety Awareness; Beauty and Skincare Products